1999
DOI: 10.1074/jbc.274.45.32225
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Factors VIIa and Xa Induce Cell Signaling Leading to Up-regulation of the egr-1 Gene

Abstract: Intracellular signaling induced by the coagulation factors (F) VIIa and Xa is poorly understood. We report here studies on these processes in a human keratinocyte line (HaCaT), which is a constitutive producer of tissue factor (TF) and responds to both FVIIa and FXa with elevation of cytosolic Ca 2؉ , phosphorylation of extracellular signal-regulated kinase (Erk) 1/2, p38 MAPK , and cJun N-terminal kinase, and up-regulation of transcription of the early growth response gene-1 (egr-1). Using egr-1 as end point,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
180
3
6

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(200 citation statements)
references
References 41 publications
11
180
3
6
Order By: Relevance
“…Factor VIIa appeared to have no e ect. However, two recent studies by Camerer et al (1999Camerer et al ( , 2000 show that PAR2 can be activated by factor VIIa, but this occurs optimally only when the VIIa is bound to tissue factor (TF) on the cell surface and factor X is present. Under these conditions, factor VIIa (and Xa) activate PAR2 with an EC 50 of approximately 8 pM.…”
Section: Par2mentioning
confidence: 99%
See 1 more Smart Citation
“…Factor VIIa appeared to have no e ect. However, two recent studies by Camerer et al (1999Camerer et al ( , 2000 show that PAR2 can be activated by factor VIIa, but this occurs optimally only when the VIIa is bound to tissue factor (TF) on the cell surface and factor X is present. Under these conditions, factor VIIa (and Xa) activate PAR2 with an EC 50 of approximately 8 pM.…”
Section: Par2mentioning
confidence: 99%
“…Factor Xa (Parry et al, 1996;Camerer et al, 2000). TF/VIIa (Camerer et al, 1999(Camerer et al, , 2000. MT-SP1 (Takeuchi et al, 2000).…”
Section: Which Receptor(s) Contribute To Thrombin Responses In Any Pamentioning
confidence: 99%
“…Several reports support the hypothesis of a key role for coagulation factors in the pathogenesis of tissue fibrosis, particularly within the kidney (8,(27)(28)(29)(30). Interestingly, earlier works suggested that FXa, the enzymatically active constituent of the prothrombinase complex, triggers complex pathways involved in the regulation of cellular growth (31,32). Binding of FXa to vascular endothelial cells induces the release of PDGF-like molecules, thus providing a paracrine mechanism for cell proliferation (33).…”
mentioning
confidence: 99%
“…They found that 24 genes increased, including cfos, EGF, and IL 1. This activation of cytokine or oncogene could promote invasive ability and MMP expression, whereas MMPs could lead to a cancer cell's extracellular matrix degradation, thus participating in the regulation of cancer cell invasion (Camerer et al, 1999). Researchers have found that TF/FVIIa complex could inhibit the apoptosis of a baby hamster's kidney cells induced by serum deprivation by activating PI3K/ Akt signal transduction (Sorensen et al, 2003;Versteeg et al, 2004).…”
Section: Discussionmentioning
confidence: 99%